Phylogenetic analysis of the complete mitochondrial genome of the orange-winged sulphur butterfly Dercas nina Mell 1913 (Insecta: Lepidoptera: Pieridae: Coliadinae) - Arlene M. Agcaoili; Nabiha Ameena; Dexter Andres; Rhey Caners; Manishvinder K. Chahal; Nicole J. Croitor; Gabrielle M. David; Kaesy L. Enns; Oleksandra Fedorova; Hannah A. Garber; Sarah D. Gregoire; Tenley E. Ilnisky; et al. (Mitochondrial DNA. Part B. Resources)
Dercas nina Mell 1913 (Pieridae) is a little-studied butterfly species endemic to China that flies primarily in the forest canopy. Genome skimming by Illumina sequencing allowed assembly of 146,702 reads for complete 1471.3-fold mean coverage of the circular 15,264 bp mitogenome from D. nina consisting of 82.1% AT nucleotides. A gene order typical of butterflies was recovered consisting of 13 protein-coding genes, 22 tRNAs, two rRNAs, and a predicted control region. The Dercas nina COX1 open reading frame begins with atypical start codon CGA. Six protein-coding genes (COX1, COX2, ND2, ND3, ND4, ND5) with single-nucleotide (T) stop codons, and two protein-coding genes (ATP6, ATP8) with two-nucleotide (TA) stop codons encoded in the DNA were inferred to be completed by adenine nucleotides from the Poly-A tail of the mRNA. Bayesian’s phylogenetic reconstruction places the D. nina and D. lycorias mitogenomes as sister clades. Dercas mitogenomes were sister to those from genus Colias in the monophyletic subfamily Coliadinae. The mitogenome phylogeny is consistent with previous molecular phylogenetic hypotheses based on other markers, but differs somewhat from a morphology-based hypothesis that suggested that Dercas was more closely related to genus Gonepteryx. This may falsify the hypothesis or may instead reflect mitochondrial-nuclear phylogenetic discordance.